2006
DOI: 10.1159/000096496
|View full text |Cite
|
Sign up to set email alerts
|

Tract Identification by Novel MRI Signal Changes following Stereotactic Anterior Capsulotomy

Abstract: Background: Five patients underwent magnetic resonance imaging (MRI) following MRI-guided stereotactic bilateral anterior capsulotomy to detect lesion-related anatomic changes. Methods: Five disabled and treatment-resistant patients with major depression (n = 4) and obsessive-compulsive disorder (n = 1) underwent stereotactic bilateral anterior capsulotomy. All patients had postoperative MRI at 2 months and at 1–4 years after surgery. An additional patient who had a pure motor deficit following a spontaneous b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 61 publications
1
21
0
2
Order By: Relevance
“…[5][6][7] In either case, the volume loss does not become visible until at least several months poststroke. [8][9][10][11][12][13] The cerebral peduncle is ideal for assessing postinfarction wallerian degeneration, because its fibers (which are corticofugal) are completely arrayed in parallel, in contrast to most other brain stem areas. 14,15 The degree of peduncular atrophy from wallerian degeneration after supratentorial infarction can be conveniently expressed by dividing the peduncular area on the atrophied side by the area on the contralateral side at the same level in the axial plane.…”
mentioning
confidence: 99%
“…[5][6][7] In either case, the volume loss does not become visible until at least several months poststroke. [8][9][10][11][12][13] The cerebral peduncle is ideal for assessing postinfarction wallerian degeneration, because its fibers (which are corticofugal) are completely arrayed in parallel, in contrast to most other brain stem areas. 14,15 The degree of peduncular atrophy from wallerian degeneration after supratentorial infarction can be conveniently expressed by dividing the peduncular area on the atrophied side by the area on the contralateral side at the same level in the axial plane.…”
mentioning
confidence: 99%
“…Fibres within the anterior limb of the internal capsule constitute three distinct fibre tracts54: (1) fibres originating in the anterior thalamic peduncle, which connect to the cingulum bundle,55 the target of anterior cingulotomy; (2) a deeper system of fibres made up of frontopontine fibres; and (3) a third set which does not run in bundles and connects the caudate nucleus and the lentiform nucleus. A recent neuroimaging study demonstrated neuronal degeneration within these three pathways in five patients after ACAPS 56. A mechanism of action for ACAPS is, as yet, unknown.…”
Section: Discussionmentioning
confidence: 98%
“…It is noteworthy that lesions placed in the AC in the past have been located in the most inferior part of the ALIC (Hurwitz et al, 2006). In a postoperative effort to demonstrate degenerating brain regions with T1-weighted MRI after anterior capsulotomies, two affected neuronal systems in depressed patients were identified.…”
Section: Discussionmentioning
confidence: 99%